Edukasi Program Perencanaan Persalinan Dan Pencegahan Komplikasi (P4k) sebagai upaya Mendukung Gerakan Desa Siaga - Mella Yuria Rachma Anandita (Surya Edukasi: Jurnal Pengabdian Masyarakat, 2025)
The maternal mortality rate (MMR) in Indonesia is still high, partly due to the low knowledge of pregnant women and families in recognizing danger signs of pregnancy and readiness to face complications. The Labor Planning and Complication Prevention Program (P4K) is the government's strategy to reduce maternal mortality rates (MMR) through community empowerment, especially in alert village areas. This community service activity aims to enhance the knowledge and skills of posyandu cadres, pregnant women, and the community regarding the P4K program through participatory-based education. Education was conducted at Posyandu Pala, Rancamaya, Bogor, involving 35 participants. The results of the pre-test and post-test showed a significant increase in participants' knowledge after the education was provided. This evidence shows that educational interventions are effective in supporting the successful implementation of P4K at the community level. Furthermore, these improvements highlight the importance of ongoing education and support for community health initiatives. By continuously engaging participants and providing them with essential resources, the program can foster a more informed and proactive approach to maternal and child health within the community. Thus, strengthening the role of cadres and cross-sector collaboration becomes key in realizing independent and responsive alert villages for maternal and child health.